If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -10 = -2x + 4 Reorder the terms: -10 + -3x = -2x + 4 Reorder the terms: -10 + -3x = 4 + -2x Solving -10 + -3x = 4 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -10 + -3x + 2x = 4 + -2x + 2x Combine like terms: -3x + 2x = -1x -10 + -1x = 4 + -2x + 2x Combine like terms: -2x + 2x = 0 -10 + -1x = 4 + 0 -10 + -1x = 4 Add '10' to each side of the equation. -10 + 10 + -1x = 4 + 10 Combine like terms: -10 + 10 = 0 0 + -1x = 4 + 10 -1x = 4 + 10 Combine like terms: 4 + 10 = 14 -1x = 14 Divide each side by '-1'. x = -14 Simplifying x = -14
| 0.6(j-2)=0.3l | | 20+x=2(20-2x) | | 14-d=45 | | x+2x+2x-30=5400 | | 8-n-3n=6 | | -6x+2y=5 | | 6x-2(-6x+3)=120 | | 2x+20=-3x+50 | | 4(x-3)+7=-3 | | 7x+2(3x+7)=144 | | 6x^2+9x-4=38 | | ax^3+bx-5=0 | | D+8=-7 | | -4(n-b)=12 | | 9(n+6)-5(2+2n)=-8n+5n | | 5(x+4)+14=59 | | 21=3(c-9) | | 6x-2(-6+3)=120 | | 3a+3b+3c=3b | | 7x-2-3x=-10 | | x+3.6=0.5 | | 2(8+4*2)= | | Y=(2t^2)+1 | | 5x+7(4x+7)=-149 | | -6(2x-7)=-12x+42 | | 6-5x=-39 | | 27x^3+9x^2+3x-3=0 | | 0.83x=35 | | 30+8=74 | | 5(k-5)-4(k+1)-13=-33 | | x=x^2-4x+2 | | Y=2t+1 |